Disulfide stoppered polyrotaxanes with enhanced cellular uptake and intracellular cyclodextrin release - Gergely Kali; Alexander H. Mayer; Dennis To; Martyna Truszkowska; Raphael Plangger; Markus Gallei; Andreas Bernkop-Schnürch (Carbohydrate Polymer Technologies and Applications)
Background and Aim: Polyrotaxanes are molecular necklaces composed of polymers, threaded macrocycles, and bulky stopper molecules to inhibit the decomposition of the first two. These supramolecular assemblies are promising active ingredients for treating lysosomal storage disorders. This study aimed to synthesize such polyrotaxanes with a novel, simple method, resulting in high threading efficacy, enhanced cellular uptake, and intracellular cyclodextrin (CD) release. Methods: In this study, we developed two novel poly(ethylene glycol) (PEG) based polyrotaxanes, with threaded α-cyclodextrin (α-CD) or its mixture with 2-hydroxypropyl-α-CD (HP-α-CD) and glutathione sensitive disulfide connected stopper molecules. The structure and composition of these polyrotaxanes were determined by 1H NMR spectroscopy and gel permeation chromatography, while the cellular uptake was investigated by flow cytometry and confocal microscopy. Results: High threading efficacy, as well as molar mass of 17.9 and 13.1 kDa, was found for the polymeric supramolecules with threaded α-CD and α-CD/HP-α-CD, respectively. Glutathion-triggered reductive removal of the stopper molecules showed potential decomposition of these polyrotaxanes in target cells. Flow cytometry revealed an up to 52-fold enhancement in cellular uptake of α- and HP-α-CD by the polyrotaxanes compared to free CD, which was also visualized by confocal microscopy. Conclusion and scope of application: Polyrotaxanes based on α-CD and its derivative were tested in vitro for application in the treatment of lysosomal storage disease for the first time. Based on these results, polyrotaxanes with disulfide stopper molecules might be promising supramolecular excipients for cellular delivery of α-CDs.